Receptor-ligand diffusion-limited reaction rates on curved membranes - Rob Daniels (Chemical Physics Letters, 2022)
We provide an expression for the diffusion-limited reaction rate on a curved surface, or membrane, in the perturbative deformation regime. This result is applied to the specific case of calculating the receptor-ligand association rate at membrane deforming, transmembrane receptor proteins, or inclusions. The dynamics of mechanochemical coupling between chemical activity and local membrane curvature is further investigated, and the effect of thermal membrane fluctuations is also discussed. It is found for transmembrane proteins, or inclusions, that their concomitant receptor-ligand reaction rates can be typically reduced by as much as 20% due to the effect of locally induced membrane curvature or geometry.